The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12958-021-00845-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and gene expression changes in mouse pre- and post-implantation embryos generated by intracytoplasmic sperm injection with artificial oocyte activation

Abstract: Background The application of artificial oocyte activation (AOA) after intracytoplasmic sperm injection (ICSI) is successful in mitigating fertilization failure problems in assisted reproductive technology (ART). Nevertheless, there is no relevant study to investigate whether AOA procedures increase developmental risk by disturbing subsequent gene expression at different embryonic development stages. Methods We used a mouse model to explore the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Recently, changes in DNA methylation and gene expression have been observed using ionomycin in a mouse model ( Yin etal. , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, changes in DNA methylation and gene expression have been observed using ionomycin in a mouse model ( Yin etal. , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, development and optimization of biotechnically efficient L1-LORD-Q-mediated approaches to identify, in a highly detectable manner, the diminished molecular quality of single fibroblasts and/or oocytes might provide an excellent tool largely applicable to the negative selection of nuclear donor somatic cells and/or nuclear recipient germ cells that seem to be genetically undesirable/unsuitable for a wide variety of modern assisted reproductive technologies (ARTs) in mice and other mammalian species. This variety of ARTs encompasses such innovative strategies of in vitro embryo production (IVP) as somatic cell nuclear transfer (SCNT)-based cloning combined or not combined with transgenesis (Song et al 2020 ; Skrzyszowska and Samiec 2021 ; Wiater et al 2021 ; Moradi-Hajidavaloo et al 2023 ) and in vitro fertilization (IVF) by either gamete coincubation (Treleaven et al 2021 ; Gorczyca et al 2022 ; Montgomery et al 2023 ) or intracytoplasmic sperm injection (ICSI) (Yin et al 2021 ; Campos et al 2023 ; Ramírez-Agámez et al 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Problems with oocyte-derived and de ciencies in downstream signaling pathways may be the main cause of infertility in women of advanced age and POI [28]. Furthermore, agerelated defects may lead to mitochondrial DNA alignment, accompanied by mitochondrial dysfunction and changes in gene expression pro le [29]. However, these studies suggested that AOA may not improve embryo development with advanced age and POI patients, but may improve fertilization rates and thus potentially provide more transferable embryos [17].…”
Section: Discussionmentioning
confidence: 99%